Study of Toxoplasma infection in Brazilian wild mammals: Serological evidence in Dasypus novemcinctus Linnaeus, 1758 and Euphractus sexcinctus Wagler, 1830 - da Silva, A. V.; Bosco, S. D.; Langoni, Hélio [UNESP]; Bagagli, E. (Elsevier B.V., 2006)
Toxoplasmosis is a worldwide distributed zoonosis that affects man and most warm-blooded animals, with a great economic impact in animal and public health. Serum samples from nine 9-banded armadillos, three 6-banded armadillos, three coatimundis, two opossums and one nutria were submitted for anti-Toxoplasma gondii antibody detection by means of a modified direct agglutination method. Encephalic tissue of three 6-banded armadillos, one 9-banded armadillo, one coatimundi and one nutria were digested in acid pepsin solution and inoculated into Swiss mice for parasite isolation. Only one serum sample from a nine-banded armadillo and two from six-banded armadillos reacted producing titers equal to 256, 512 and 512, respectively. T gondii was isolated in two 6-banded armadillos, one of which was not positive in the serological test. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Toxoplasma gondii; wild mammals; serology; modified agglutination test; bioassay in mice